Vascularized Composite Allograft Rejection Is Delayed by Intrajejunal Treatment with Donor Splenocytes without Concomitant Immunosuppressants. (27th November 2012) - Wallace, Christopher Glenn; Yen, Chia-Hung; Yang, Hsiang-Chen; Lin, Chun-Yen; Wu, Ren-Chin; Huang, Wei-Chao; Lin, Jeng-Yee; Wei, Fu-Chan
Abstract : Background . Mucosal or oral tolerance, an established method for inducing low-risk antigen-specific hyporesponsiveness, has not been investigated in vascularized composite allograft (VCA) research. We studied its effects on recipient immune responses and VCA rejection. Methods . Lewis rats (n = 12 ; TREATED) received seven daily intrajejunal treatments of 5 × 10 7 splenocytes from semiallogeneic Lewis-Brown-Norway rats (LBN) or vehicle (n = 11 ; SHAM). Recipients' immune responses were assessed by mixed lymphocyte reaction (MLR) against donor antigen and controls. Other Lewis (n = 8 ; TREATED/VCA) received LBN hindlimb VCA and daily intrajejunal treatments of 5 × 10 7 LBN splenocytes, or LBN VCA without treatment (n = 5 ; SHAM/VCA), until VCAs rejected. Recipients' immune responses were characterised and VCAs biopsied for histopathology. Immunosuppressants were not used. Results . LBN-specific hyporesponsiveness was induced only in treated Lewis recipients. Treatment significantly reduced MLR alloreactivity, significantly reduced VCA rejection on histopathology, and significantly delayed clinical VCA rejection (P < 0.0005 ; TREATED/VCA mean 9.6 versus 6.0 days for SHAM/VCA). Treatment significantly increased immunosuppressive IL-10/IL-4/TGF- β production and significantly decreased proinflammatory IFN- γ /TNF- α . Conclusion . Jejunal exposure to antigen conferred donor specific hyporesponsiveness that delayed VCA rejection. This method may offer a low-risk adjunctive treatment option to help protect VCAs from rejection.